Pengaruh Pengetahuan dan Pergaulan Bebas Terhadap Orang Tua Menikahkan Anak Pada Usia Muda di Desa Bangunrejo Kecamatan Tanjung Morawa - Lubis, Juli Ana (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Early marriage is a marriage of below 20 year-old teenagers who are actually not ready to get married. Adolescence is the period of vulnerability to the risk for pregnancy because of early marriage such as miscarriage, premature childbirth, BBLR, congenital defects, easy to be infected, anemia in pregnancy, eclampsia, and death. The objective of the research was to Influence of Knowledge and Free Relationship on parents to marry their young children off at Bangun Rejo Village, Tanjung Morawa Subdistrict. The research used observational analytic quantitative method with case control design. The population was 37 parents who married their young children off as cases and 37 parents who did not marry their young children off as controls. The data were gathered by using questionnaires abd process and analyzed by using chi square test and multiple logistic regression analysis.The result of the research showed that there was the influence of knowledge and promiscuity.It is recommended that life quality of adolescents and children be increased in arts and performance which can help family income. Motivation should be given to children so that they can achieve their goal and reduce the incidence of early marriage by doing activities.